2020
DOI: 10.1080/21665095.2020.1798261
|View full text |Cite
|
Sign up to set email alerts
|

Environmental sustainability and financial development in Africa; does institutional quality play any role?

Abstract: The Environmental Kuznets Curve (EKC) having been used to explain the relationship between growth and environmental degradation has gained some attention in the finance literature in recent times. In this study, we re-conceptualize the EKC into a Financial Market Environmental Kuznets Curve (FMECK) that explains the relationship between financial development and sustainability, while introducing institutional quality as a moderator. The study posits that there is an Environmental Kuznets Curve for Africa and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 51 publications
(37 reference statements)
5
47
1
Order By: Relevance
“…Different viewpoints on the impact of financial development on energy intensity or consumption can be found in the extant relevant literature. One view is that more financial development will result in increased energy consumption or energy intensity ( Ntow-Gyamfi et al., 2020 ). Sadorsky (2010 , 2011) found that financial development promoted energy consumption in 22 rising economies and nine border economies in Eastern and Central Europe.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Different viewpoints on the impact of financial development on energy intensity or consumption can be found in the extant relevant literature. One view is that more financial development will result in increased energy consumption or energy intensity ( Ntow-Gyamfi et al., 2020 ). Sadorsky (2010 , 2011) found that financial development promoted energy consumption in 22 rising economies and nine border economies in Eastern and Central Europe.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Subsequently (Sah, 2021) suggested the need to clean up the institutional arrangement by improving GE, anti-corruption mechanisms, regulatory compliance and the implementation of legal and institutional reforms to ensure that they have a high institutional quality to deal with environmental issues. Ntow-Gyamfi et al (2020) found that a strong institutional framework helps to mitigate the long run adverse effects of financial development on CO 2 emissions, and that improving institutional quality is more likely to promote sustainable development in South Asia (Hunjra et al, 2020). Furthermore, institutional quality, trade, openness and financial development are the main factors to enhance environmental quality (Ahmed et al, 2020).…”
Section: Institutional Quality Related To Co 2 Emissionsmentioning
confidence: 99%
“…(1997) and Barbier (1997) are among the early studies that provide evidence for the EKC hypothesis. For SSA, Ntow-Gyamfi et al. (2020), Bah et al.…”
Section: Literature Reviewmentioning
confidence: 99%